Inhibitory effect of fucoidan on the activities of crotaline snake venom myotoxic phospholipases A2 - Angulo Ugalde, Yamileth (2003)
Myotoxic phospholipases A2 account for most of the muscle necrosis that results from envenenomation by crotaline snakes. In this study, we investigated the protective effect of fucoidan, a natural sulfated polysaccharide obtained from the brown seaweed Fucus vesiculosus, against the cytotoxic and myotoxic activities of a group of phospholipase A2 myotoxins from crotaline snake venoms: Bothrops asper myotoxins I, II, III, and IV, Cerrophidion godmani myotoxins I and II, Atropoides nummifer myotoxins I and II, and Bothriechis schlegelii myotoxin I. All of the toxins tested were efficiently inhibited by fucoidan, in both their cytotoxic and myotoxic effects. The basis for this inhibition appears to be the rapid formation of complexes between fucoidan and myotoxins, as evidenced by turbidimetric analysis. The possible binding site of fucoidan on the myotoxins was investigated using short synthetic peptides that represent the membrane-damaging region (residues 115–129) for three of these toxins. Fucoidan clearly inhibited the cytolytic activity of the peptides, indicating its ability to interact with the C-terminal myotoxic region of these phospholipases A2. Fucoidan significantly inhibited muscle damage in mice, when administered locally, immediately after experimental envenomation with crude venom from B. asper. These results encourage further studies of sulfated fucans as compounds of potential use to improve the treatment of envenomations by crotaline snakes.